Revisiting value in capitalist natures: Rent, class, liberation. Issue 1 (March 2020) - Kay, Kelly; Kenney-Lazar, Miles
Prompted by a 'further engagement' piece written by Elisa Greco and Elia Apostolopoulou, we revisit our published articles, 'Value in Capitalist Natures: An Emerging Framework' and 'Valuing Nature Within and Beyond Capitalism: A Response'. First, we address concerns over our conceptual understandings of the relationships between value and nature, and we raise some of the opportunities and challenges presented by orienting nature–society scholarship around rent and class. Second, we explore what we have called the 'liberatory valuation of nature', raising the point that value and capital are related but not synonymous, and arguing that value does not present an impediment to alternative futures, but instead can serve as a bridging concept between present and future socio-ecological, economic, and political configurations. We close by revisiting the potential opportunities of a 'value in capitalist natures' framework that bridges heterodox political–economic notions of value with more-than-capitalist ones.